Dampak Rasio Keuangan terhadap Kebijakan Dividen dengan Moderasi Ukuran Perusahaan pada Perusahaan Sektor Consumer Goods yang Terdaftar di Bursa Efek Indonesia - Eni Tri Indarwati; Dhani Ichsanuddin Nur (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The company's dividend policy specifies how dividends will be paid while taking into account the level of profit the company generates. This study looked at how profitability, debt, and liquidity affected dividend policies in companies in the consumer products sector listed on the Indonesia Stock Exchange between 2018 and 2021, with company size acting as a moderating factor. The method used in this research is Moderated Regression Analysis (MRA). The results of this study indicate that liquidity contributes to dividend policy, leverage contributes to dividend policy and profitability contributes to dividend policy. While liquidity which is moderated by company size can contribute to dividend policy, leverage which is moderated by company size can contribute to dividend policy and Profitability which is moderated by company size can contribute to dividend policy. Keywords: Company Size; Dividend Policy; leverage; Liquidity; Profitability.